2018
DOI: 10.3390/rs10020282
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Coastal Sea Level Offshore Hong Kong from Jason-2 Altimetry

Abstract: Abstract:As altimeter satellites approach coastal areas, the number of valid sea surface height measurements decrease dramatically because of land contamination. In recent years, different methodologies have been developed to recover data within 10-20 km from the coast. These include computation of geophysical corrections adapted to the coastal zone and retracking of raw radar echoes. In this paper, we combine for the first time coastal geophysical corrections and retracking along a Jason-2 satellite pass that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Both the missions provide valid performance due to our numerical test and the agreement is slightly better for in situ/SARAL than for in situ/HY-2A. We also calculated the correlation coefficients for the tide gauge sites used for validation in the recent published studies [28,29]. Four UHSLC sites (Los Angeles, CA; Cape May, NJ; Ko Lak; Hong Kong) with required data series were selected due to the time-scope repetition with HY-2A and SARAL.…”
Section: Validation With Tide Gauge Measurementsmentioning
confidence: 86%
“…Both the missions provide valid performance due to our numerical test and the agreement is slightly better for in situ/SARAL than for in situ/HY-2A. We also calculated the correlation coefficients for the tide gauge sites used for validation in the recent published studies [28,29]. Four UHSLC sites (Los Angeles, CA; Cape May, NJ; Ko Lak; Hong Kong) with required data series were selected due to the time-scope repetition with HY-2A and SARAL.…”
Section: Validation With Tide Gauge Measurementsmentioning
confidence: 86%
“…Some results are reported here, in which the sea level for a certain cycle is the average of all the valid measurements within ≀10 distance from the coast. Interested readers can refer to [41] for more details.…”
Section: Resultsmentioning
confidence: 99%
“…In the Hong Kong offshore case study, we find that the coastal sea level trend is about twice as much as the one observed further offshore (which can be inferred as +2.7 mm/yr. from the ESA Sl_CCI product [41]). It suggests that in the Hong Kong region, the short-term sea level trend significantly increases when approaching the coast.…”
Section: Conclusion and Prospectivementioning
confidence: 99%
“…A table is published in Cipollini et al (2017) and a regularly updated version is available at http://www.coastalt.eu/#datasets. Several studies compared these data sets with independent measurements (e.g., GĂłmez-Enri et al, 2016;Vu et al, 2018;Xu et al, 2018). Quality assessments for Sentinel-3A and CryoSat-2 (Bonnefond et al, 2018a;Fenoglio et al, 2019) and AltiKa data (Bonnefond et al, 2018b) have also been performed.…”
Section: Level 3 Altimetry Datasetsmentioning
confidence: 99%